Case Study: Successful Rehabilitation of a Torn Rotator Cuff through Physical Therapy for Positive Functional Recovery - Muhammada Mahnoor, Muhammad Waseem Akhtar, Quratulain Maqsood, Muhammad Mahmood Alam, Rabiya Noor, (Pakistan Journal of Medical & Health Sciences, 2023)
Older adults often suffer from shoulder pain. Rotator cuff problems are typically responsible for shoulder pain. The majority of rotator cuff disorders can be treated conservatively. Shoulder issues are rather common. More than 30% of people have shoulder pain at some time in their lives. Shoulder discomfort is one of the most frequent musculoskeletal problems in people over the age of 65. The rotator cuffs are four muscles that connect the top arm bone (humerus) to the upper shoulder blade (scapula). If the rotator cuff is injured, every motion on the affected shoulder, including flexion, extension, abduction, adduction, and internal and external rotation, may be difficult. Having a rotator cuff tear restricts movement of the shoulder, which makes it difficult for the patient to do everyday tasks such as getting dressed or washing their hair. They may also find it difficult to remove something from their back pockets. patient was completely immobile when injured. Treatment was provided for up to three months, and almost 30 rehabilitation sessions were conducted during this time. In each rehabilitation session, patients were treated with electrotherapeutic modalities, dry cupping, and manual therapy exercises. The rehabilitation session lasted up to an hour. After one month of rehabilitation, the shoulder pain was noticeably reduced and nearly gone. Following the treatment, she achieved the most improvement in her functional capacity. For instance, she is now able to put on clothes without any assistance. Now she can comb her hair on her own. It was proven that exercise treatment significantly reduced pain and improved function in individuals with fully ruptured or torn supraspinatus and infraspinatus tendons. Keywords: Rotator cuff, full thickness tear, disability, surgery, shoulder pain, physical therapy.